The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/resources4030577
|View full text |Cite
|
Sign up to set email alerts
|

A Columbia River Basalt Group Aquifer in Sustained Drought: Insight from Geophysical Methods

Abstract: Aquifers within the Columbia River Basalt Group (CRBG) provide a critical water supply throughout much of the Pacific Northwest of the United States. Increased pumping has resulted in water level declines in this region. Recharge into this aquifer system is generally not well understood. Recent suggestions of probable decades-long droughts in the 21st century add to this problem. We show that geophysical methods can provide useful parameters for improved modeling of aquifers in a primary CRBG aquifer located o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This probably implies that a significant amount of water might be entering as recharge to GR to balance the deficit. In a recent study, Piersol and Sprenke [61] indicated that about 93.5% ± 2.6% of water in GR is contributed by the recharge which agrees the finding this study (Figure 7). Figure 7 shows the contribution of recharge to GR as a percentage.…”
Section: Simulation Of Groundwater Volume Of the Aquiferssupporting
confidence: 82%
See 4 more Smart Citations
“…This probably implies that a significant amount of water might be entering as recharge to GR to balance the deficit. In a recent study, Piersol and Sprenke [61] indicated that about 93.5% ± 2.6% of water in GR is contributed by the recharge which agrees the finding this study (Figure 7). Figure 7 shows the contribution of recharge to GR as a percentage.…”
Section: Simulation Of Groundwater Volume Of the Aquiferssupporting
confidence: 82%
“…The answer might not be straightforward and probably the most up-to-date explanation can be considered to be the approach adopted by [45]. This study keeps on the paradigm that GR may be actively recharging based on the water balance model which is supported by some of the most current studies [61,62]. Figure 5 shows that with an increase of water demand in GR, recharge from WP to GR is also consistently increasing until it reaches the threshold.…”
Section: Simulation Of Groundwater Volume Of the Aquifersmentioning
confidence: 78%
See 3 more Smart Citations